2020
DOI: 10.4236/ojog.2020.1020018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Extreme Maternal Ages on Hypertensive Disorders of Pregnancy: A Retrospective Cohort Study in Dakar, Senegal

Abstract: Background: Hypertensive disorders of pregnancy are a frequent situation and involve about 8%-10% of pregnancies. Extremes maternal ages have been associated to hypertensive disorders of pregnancy. In Africa, even if motherhood in teens is common, pregnancy at advanced age is getting more and more frequent. Objectives: To investigate the relation between maternal age and hypertensive disorders of pregnancy. Methods: A retrospective cohort study over 8 years was conducted in a suburb setting in Dakar, Senegal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Some authors link placental laterality and the high risk of hypertension in pregnant women [35,36], which also coincides with our findings. The development of eclampsia can also be associated with adolescence, and age over 35 years -with hypertension [28]. Thus, our work clearly shows the risk factors and presents a screening model for PE.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Some authors link placental laterality and the high risk of hypertension in pregnant women [35,36], which also coincides with our findings. The development of eclampsia can also be associated with adolescence, and age over 35 years -with hypertension [28]. Thus, our work clearly shows the risk factors and presents a screening model for PE.…”
Section: Discussionmentioning
confidence: 53%
“…Numerous scientific studies have concluded that older age (35 years) and an increase in BMI before pregnancy (25 kg/m 2 ) are considered moderate risk factors for PE [25][26][27][28][29][30][31]. A high rate of PE is associated with the study selection of pregnant women with maternal risk factors according to FIGO recommendations [5].…”
Section: Discussionmentioning
confidence: 99%